Developing cortex is functionally pluripotent: Evidence from blindness - Elizabeth J. Saccone; Mengyu Tian; Marina Bedny (Developmental Cognitive Neuroscience, 2024)
How rigidly does innate architecture constrain function of developing cortex? What is the contribution of early experience? We review insights into these questions from visual cortex function in people born blind. In blindness, occipital cortices are active during auditory and tactile tasks. What ‘cross-modal’ plasticity tells us about cortical flexibility is debated. On the one hand, visual networks of blind people respond to higher cognitive information, such as sentence grammar, suggesting drastic repurposing. On the other, in line with ‘metamodal’ accounts, sighted and blind populations show shared domain preferences in ventral occipito-temporal cortex (vOTC), suggesting visual areas switch input modality but perform the same or similar perceptual functions (e.g., face recognition) in blindness. Here we bring these disparate literatures together, reviewing and synthesizing evidence that speaks to whether visual cortices have similar or different functions in blind and sighted people. Together, the evidence suggests that in blindness, visual cortices are incorporated into higher-cognitive (e.g., fronto-parietal) networks, which are a major source long-range input to the visual system. We propose the connectivity-constrained experience-dependent account. Functional development is constrained by innate anatomical connectivity, experience and behavioral needs. Infant cortex is pluripotent, the same anatomical constraints develop into different functional outcomes.